Comparison of Gestational Weight Gain z‐Scores and Traditional Weight Gain Measures in Relation to Perinatal Outcomes. Issue 1 (10th December 2014) - Bodnar, Lisa M.; Hutcheon, Jennifer A.; Parisi, Sara M.; Pugh, Sarah J.; Abrams, Barbara
Abstract Background Conventional measures of gestational weight gain (GWG) are correlated with pregnancy duration, and may induce bias to studies of GWG and perinatal outcomes. A maternal weight‐gain‐for‐gestational‐age z‐score chart is a new tool that allows total GWG to be classified as a standardised z‐score that is independent of gestational duration. Our objective was to compare associations with perinatal outcomes when GWG was assessed using gestational age‐standardised z‐scores and conventional GWG measures. Methods We studied normal‐weight (n = 522 120) and overweight (n = 237 923) women who delivered liveborn, singleton infants in Pennsylvania, 2003–11. GWG was expressed using gestational age‐standardised z‐scores and three traditional measures: total GWG (kg), rate of GWG (kg per week of gestation), and the GWG adequacy ratio (observed GWG/GWG recommended by the Institute of Medicine). Log‐binomial regression models were used to assess associations between GWG and preterm birth, and small‐ and large‐for‐gestational‐age births, while adjusting for race/ethnicity, education, smoking, and other confounders. Results The association between GWG z‐score and preterm birth was approximately U‐shaped. The risk of preterm birth associated with weight gain <10th percentile of each measure was substantially overestimated when GWG was classified using total kilogram and was moderately overestimated using rate of GWG or GWG adequacy ratio. All GWG measures had similar associations with small‐ or large‐for‐gestational‐age birth. Conclusions Our findings suggest that studies of gestational age‐dependent outcomes misspecify associations if total GWG, rate of GWG, or GWG adequacy ratio are used. The potential for gestational age‐related bias can be eliminated by using z‐score charts to classify total GWG.